Liberty Equality Power - Murrin, John. (Philadelphia Harcourt Brace and Company, 1996)
This book attempts to integrate social and cultural history into a political story. We havetried not to ghettoize the concerns and achievenents of women, Indians, African American, Hispanics, Asians and other minorities.
Keywords: History